P-153 The cost of the overnight service at rennie grove hospice care versus the cost of an acute admission. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Clarke, Jo; Varvel, Sue
Abstract : Background: Rennie Grove Hospice Care (RGHC) runs a Hospice at Home service providing 24/7 care. An independent study calculated the cost of a RGHC visit and the total community cost of home care, including all health care professional (HCP), carer, and family member visits. Methods: Over a period of 145 days, 550 calls and 335 visits made to/by the night team were recorded, averaging 3.79 per night. The salary cost per hour for each nurse, plus organisational add-on costs, was calculated. To derive a total community cost, 35 families, considered by the nursing team to be able to consent, kept a diary for up to two-weeks, recording all HCP, carer and family support visits and duration of each visit. Seventeen diaries were returned. Descriptive analysis was used with the Statistical Package for the Social Sciences (SPSS v22). Costs were taken for HCPs and social care services from the Personal Social Services Research Unit data 2015/16. Results: For 3.79 visits per night the cost per visit was £195 (taking into consideration that RGHC nurses travel in pairs). The 17 patient diaries covered a total of 177 days and showed a range of visits and complexity of care. RGHC staff provided 19% of the care at a cost of £3295; district nurses 13%, cost £2005; and formal carers 55% at a cost of £1344. 23 GPs visits comprised 4% of all visits but 15% of total costs. Macmillan/Marie Curie nurses accounted for just 2% of visits but 19% of cost as they stayed overnight. The entire cost of 177 days of care for 17 patients at end of life was £11, 814; i.e. £66.7 per day as care was not needed every day of each diary period. The average length of the diaries was 10.4 days. Conclusions: The cost of home care seems acceptable, compared to the national average cost of a day in an inpatient specialist palliative care bed at £397–£400 (Data.Gov.UK 2015).